Atomski interferometer - Strnad, Janez (Obzornik za matematiko in fiziko, 2012)
Atom interferometers use waves, attributed to particles, as older interferometers use light. In the article phenomena are discribed on which atom interference with clouds of cold alkali atoms are based as well as precise measurements with them.
Keywords: curki delcev; fazna razlika; fizika; interferenca; Rabijeve oscilacije; Ramanov pojav